Prevalence of anxiety and associated factors among women undergoing gynecological surgery: A cross-sectional study - Chung, Nguyen Thi Thuy; Gam, Nguyen Thi Hong; Thu, Nguyen Ngoc; Thanh, Le Phuong; Lieu, Pham Thi; Thiet, Nguyen Ba (Tạp chí Nghiên cứu Y học, 2025)
This study aimed to evaluate the prevalence and associated factors of anxiety among women scheduled for gynecological surgery. Conducted as a cross-sectional analysis, data collection involved structured interviews that assessed demographics, clinical history, perceptions of postoperative recovery, comprehension of surgical risks, and levels of social support. Anxiety was measured using the GAD-7 scale, and associations between anxiety severity and related factors were examined through ordinal logistic regression. Among the 300 participants, all reported some degree of anxiety, with 60% experiencing mild anxiety, 30% moderate, and 10% severe. Higher anxiety levels were notably linked to limited social support and lower comprehension of counseling. The high prevalence of anxiety observed underscores the need for comprehensive preoperative communication and robust support systems. These strategies could play a vital role in reducing anxiety, ultimately contributing to improved surgical recovery and overall patient well-being.